Force majeure in extension of time - Sanis, Kathleen (2008)
Time is extremely important issue in construction. Most of construction contract specify time to complete the construction work. However, during the execution of the contract, circumstances may arise and leads to delay. In circumstances that delay occurs, the employer is entitled to claim for damages but time of completion also can be extended if the delay is caused by the relevant event which provided in extension of time provision in construction contract. One of the relevant events is force majeure. What is the definition of force majeure that applies in construction contract What are the circumstances that are accepted as force majuere event in claiming for extension of time The study aimed is to determine the meaning of a force majeure clause as the relevant events of extension of time. The findings of this study will assist to reduce uncertainty or difficulties in the event that relate to claiming of extension of time under the event of force majeure. The approach adopted in this research is law based cases. There are no limitations as for the court cases referred to in this study in terms of type of projects as long as the case is related to the force majeure event in claiming of extension of time. A total of six cases focusing on what is the interpretation of force majeure were studied. Through the analysis of court’s judgments, the meaning of force majeure in extension of time have been determined. Force majeure means all circumstances independent of will of man, and which it is not in his power to control or responsibility which is caused by a superior force or irresistible force or overwhelming power.